1H-phosphiranes and -enes invert at phosphorus via a turnstile rotation - Göller, Andreas H.; Clark, Timothy (Chemical Communications, 1997)
Ab initio (CCSD(T)/6-31+G*) calculations suggest that 1H-phosphiranes and 1H-phosphirenes invert their configuration at phosphorus by a rotation of the PX group (X = H, F, Cl, Br) above the C-2 moiety, rather than the more usual planar trigonal inversion pathway via a C-2v transition state.